2011
DOI: 10.1179/102453311x13025568941961
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of BCL11B expression inhibits proliferation and induces apoptosis in malignant T cells by BCL11B-935-siRNA

Abstract: To screen the highly efficient and specific B-cell chronic lymphocytic leukemia/lymphoma 11B (BCL11B) small interfering RNA (siRNA) which are able to downregulate the BCL11B gene expression in human T-cell acute lymphoblastic leukemia, thereby inhibiting the leukemic T-cell proliferation and inducing apoptosis, four BCL11B-siRNAs and the scrambled non-silencing siRNA control (sc) were designed and obtained by chemosynthesis. After nucleofection, BCL11B expression in the mRNA and the protein levels were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…Our findings are in accordance with the known antiapoptotic role of BCL11B in T-cell malignancies (18)(19)(20). Recently, it has been shown that BCL11B is one of the necessary genes for T-cell differentiation and is associated with T-cell malignancies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in accordance with the known antiapoptotic role of BCL11B in T-cell malignancies (18)(19)(20). Recently, it has been shown that BCL11B is one of the necessary genes for T-cell differentiation and is associated with T-cell malignancies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the prior inactivation of the highly expressed endogenous BCL11B proteins will rapidly inhibit the proliferation of Jurkat cells and induce apoptosis (51,64). To obtain further evidence of the specific involvement of PKC in regulating BCL11B interactions with MTA1 and P300, Jurkat cells were activated in the presence of a pan-PKC inhibitor, Gö6983.…”
Section: Resultsmentioning
confidence: 99%
“…However, our study did not specifically examine the Th1 and Th2 subsets, and more experiments are needed to verify whether BCL11B can regulate Th1 differentiation in human naive T cells. We and others have reported that BCL11B loss may induce apoptosis in malignant T cells such as Jurkat, huT78, and Molt-4; however, the detailed cell death mechanisms are not fully understood [16,18]. The mitochondrial apoptotic pathway [32], BCL-2 family genes [17,33], the TNF-related apoptosis inducing ligand pathway [17,34], and the transforming growth factor-␤ signaling pathway may be involved.…”
Section: Discussionmentioning
confidence: 93%
“…BCL11B overexpression was confirmed by comparing the pBCL11B and pI2 groups, and BCL11B knockdown was determined by comparing the si-935 and SC groups. MOCK nucleofected without plasmids and siRNA and NC served as controls [18].…”
Section: Transfectionmentioning
confidence: 99%